The Influence of Liquid on the Outcome of Halogen-Bonded Metal–Organic Materials Synthesis by Liquid Assisted Grinding - Katarina Lisac (Crystals, 2017)
In this work, we describe novel multi-component halogen bonded solids of Co(ii) complexes and 1,4-diiodotetrafluorobenzene, 14tfib. We present the important influence of liquid on the outcome of liquid assisted grinding of dichlorobis(1,10-phenantroline)cobalt(ii), CoCl2(phen)2 and 14tfib. Grinding of solid reactants with a small amount of water gives the cocrystal product [CoCl2(phen)2](14tfib) (1) while grinding with a small amount of methanol gives an ionic structure, the four-component solid [CoCl(MeOH)(phen)2]Cl(14tfib)(MeOH) (2). Both solid products were also obtained by crystallization from the solution. Single crystal X-ray diffraction reveals that the dominant supramolecular interaction in 1 is the I···Cl halogen bond between 14tfib and CoCl2(phen)2 building blocks. On the other hand, the dominant supramolecular interactions in 2 are I···Cl− charge-assisted halogen bonds between the halogen bond donor and the chloride anion as well as hydrogen bonds between the chloride anion and OH groups of coordinated and solvated methanol molecules.